Pengelolaan Kenaikan Pangkat PNS Berbasis SIASN Berdasarkan Peraturan BKN Nomor 4 Tahun 2023 di Kabupaten Madiun - Gangsar Ginayuh; Slamet Muchsin; Afifuddin Afifuddin (Jayapangus Press, 2026)
The application of Regulation of the National Civil Service Agency (BKN) Number 4 of 2023, which extends the promotion submission period for civil servants (PNS) from two to six times per year, represents a digital reform in personnel management. This research intends to evaluate the execution of promotional services through the State Civil Apparatus Information System (SIASN), examine the effects of the policy, and recognize difficulties challenges. A descriptive qualitative approach was employed, with data collected through in depth interviews, observations, and document analysis involving personnel administrators and civil servants as service users. Data were analyzed interactively through data reduction, data display, and conclusion drawing. The results indicate that the policy has improved efficiency, transparency, and service certainty in personnel administration. However, the increased service frequency has led to a higher workload for verification officers and persistent challenges related to document readiness, digital literacy gaps, and limited service responsiveness and empathy. The novelty of this study lies in demonstrating that increased service frequency and digitalization do not automatically translate into comprehensive service quality improvement, highlighting the need for strengthening human resource capacity and supporting systems to ensure sustainable and adaptive personnel policy implementation.